Ribotyping of Lactobacillus casei group strains isolated from dairy products - Svec, P; Dráb, V; Sedlácek, I (Folia microbiologica, 2005)
A series of lactobacilli isolated from dairy products were characterized using biotyping and ribotyping with EcoRI and HindIII restriction enzymes. Biotyping assigned 14 strains as Lactobacillus casei, 6 strains as Lactobacillus paracasei subsp. paracasei and 12 as Lactobacillus rhamnosus. The obtained ribotype patterns separated all analyzed strains into two clearly distinguished groups corresponding to L. rhamnosus and L. casei/L. paracasei subsp. paracasei. The HindIII ribotypes of individual strains representing these two groups were visually very similar. In contrast, EcoRI ribotyping revealed high intraspecies variability. All ribotypes of L. casei and L. paracasei subsp. paracasei dairy strains were very close and some strains even shared identical ribotype profiles. The type strains L. casei CCM 7088T (= ATCC 393T) and Lactobacillus zeae CCM 7069T revealing similar ribopatterns formed a separate subcluster using both restriction enzymes. In contrast, the ribotype profile of L. casei CCM 7089 (= ATCC 334) was very close to ribopatterns obtained from the dairy strains. These results support synonymy of L. casei and L. paracasei species revealed by other studies as well as reclassification of the type strain L. casei CCM 7088T as L. zeae and designation of L. casei CCM 7089 as the neotype strain.
Keywords: Species Specificity; mléčné výrobky; ribotypizace; Lacticaseibacillus casei; Phenotype; Lactobacillus casei; Lacticaseibacillus rhamnosus; Ribotyping; druhová specificita; fenotyp; Dairy Products